Thrombin generation before and after multicomponent blood collection - Cimenti, C.; Sipurzynski, S.; Gallistl, S.; Rosenkranz, A.; Hiden, M.; Leschnik, B.; Schallmoser, K.; Lanzer, G.; Muntean, W. E. (Hämostaseologie, 2008)
IThe development of apheresis technology has increased efficiency in donor blood use by collecting specific blood components in several combinations. The question of donor safety raised by the contact of donor blood with foreign, only in part biocompatible surfaces remains. The aim of this study was to estimate the effect of multicomponent blood collection on thrombin generation performing an overall function test of coagulation. Donors, methods: 26 blood donors were included. Per apheresis two units of platelets and one unit of RBCs were collected by two cell separators (Amicus® and Trima Accel®). Each donor underwent the procedure on both apheresis systems. Samples were collected before, immediately after, and 48 hours after apheresis. Thrombin generation was measured by means of calibrated automated thrombography (CAT). Results: CATdata changed only slightly and no significant changes were seen before, immediately after, and 48 hours after apheresis. The parameters did not differ significantly between the two different apheresis devices. Conclusion: No change in parameters of continuous thrombin generation occurred, suggesting that apheresis did not lead to severe alterations in the haemostatic system.
Keywords: Thrombin generation; multicomponent blood collection; haemostasis